Nonexplosion and Pathwise Uniqueness of Stochastic Differential Equation Driven by Continuous Semimartingale with Non-Lipschitz Coefficients - Jinxia Wang (Journal of Mathematics)
We study a class of stochastic differential equations driven by semimartingale with non-Lipschitz coefficients. New sufficient conditions on the strong uniqueness and the nonexplosion are derived for d-dimensional stochastic differential equations on Rd (d>2) with non-Lipschitz coefficients, which extend and improve Fei’s results.